Nurse worry as a trigger for rapid response team activation improving outcomes: a retrospective cohort study in non-critical units - Luana L.S. Gentil; Milena S. Nascimento; Michele Jaures; Leonardo P. de Carvalho; Claudia R. Laselva; Simone Brandi (BMC Nursing)
Abstract Background Patients hospitalized outside of monitored environments may experience sudden clinical worsening requiring transfer to the Intensive Care Unit. Early detection based on the clinical nurse’s identification of the risk of clinical deterioration represents an opportunity to prevent serious adverse events. Nurse worry is defined as the use of clinical reasoning combined with intuition that precedes the patient’s clinical deterioration. Objective The objective of this study was to evaluate nurse worry as a trigger for rapid response team activation in patients hospitalized in non-critical units and its association with the need in ICU admission. Methods This retrospective cohort study utilized data retrieved from an anonymized institutional database used to monitor the actions of the rapid response team. Data collected from January 2021 to December 2022 were analyzed, encompassing patients over 18 years old admitted to non-critical units and evaluated by the rapid response team. Analyzed variables included demographic characteristics, MEWS score, and causes for activating the rapid response team, such as changes in vital signs and nurse worry. Main outcomes assessed were transfer to the ICU, medical procedures, and drug administration. Patients were divided into three groups for analysis: those triggered for RRT assessment exclusively by changes in vital signs, those triggered exclusively by nurse worry and those triggered by the nurse worry combined with changes in vital signs. Results A total of 4634 rapid response team consultations were included, with 1574 triggered by changes in vital signs, 1263 triggered by nurse worry and 1797 triggered by the nurse worry associated with changes in vital signs. The group with nurse concern showed a lower need for transfers to the ICU (40%) compared to the group with changes in vital signs (50%) p < 0.001 although there was no difference in relation to the need for medical procedures,17% in both groups. Conclusion The NW emerges as a relevant factor in triggering RRT and may be associated with improved outcomes, such as reduced need for ICU transfers. However, the observational design of the study does not allow for establishing causal relationships.